P246 Persistence of Chlamydial genital infection – how common is it?. (30th June 2016) - Dhar, Jyoti; Colver, Helen; Horner, Patrick
Abstract : Background/introduction: We present a case of long term persistence of urethral chlamydia in a patient for over 1year, despite multiple treatments. We have not found any such case documented in the literature. Aims/Objective: This case raises certain questions? Could this be happening more often in patients? If yes, what is the significance? May this also explain why CT-positive patients are more likely to re-test positive within 2 yrs? Methods: In Jan 2015 a Slovakian man and his Czech female partner attend for asymptomatic sexual health screen. They were diagnosed with urethral and cervical Chlamydial infection respectively and were treated with a stat dose of Azithryomycin1gm. The only history of note is the female had had treatment for UTI requiring prolonged Nitrofurantion and the male CSW contact 3yrs ago. No other sexual partners were reported. Rescreen in March 2015 showed persistence of chlamydial urethral infection in the man while the female partner was negative. Results: Conclusion: Whilst untreated cases of chlamydial infection can resolve, to our knowledge this is the first case of persistent low load infection in a treated case and so is intriguing. It is unlikely to represent residual DNA after such a long period as in this case. The clinical significance of this is uncertain as he remained asymptomatic. The female partner was cured suggesting its not related to genotype and rectal carriage was excluded.